Molecular design principles for bipolar spindle organization by two opposing motors - Wei-Xiang Chew; François Nédélec; Thomas Surrey (Proceedings of the National Academy of Sciences, 2025)
During cell division in animal cells, a bipolar spindle assembles to segregate the chromosomes. Various motor proteins with different properties are essential for spindle self-organization. The minimal set of components required to organize dynamic microtubules into a bipolar network remains however unknown. Here, we use computer simulations to explore whether two types of microtubule-crosslinking motors with opposite directionality can organize dynamic microtubules into bipolar spindles in three-dimensional space around a local microtubule nucleation source. We find that two motors are indeed sufficient, provided their properties resemble the main human spindle motors kinesin-5 and dynein, revealing the core mechanism of spindle self-organization. It is based on the synergistic interplay of a slow plus-directed symmetric motor and a fast minus-directed asymmetric motor. A hypothetical symmetric minus-directed motor can also support spindle formation together with kinesin-5, but only in a limited and unphysiological parameter range. In agreement with its accessory role in human cells, a minus motor with human kinesin-14 properties does not assemble stable bipolar spindles together with kinesin-5. These results reveal fundamental principles for the self-organization of dynamic bipolar microtubule architectures and highlight how distinct molecular designs of mitotic motors are optimized for their task.